2014
DOI: 10.1002/adsc.201400502
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Squaramide Catalysts with the Same Absolute Chirality for the Diastereodivergent Access to Densely Functionalised Cyclohexanes through Enantioselective Domino Reactions. Synthesis and Mechanistic Studies

Abstract: We have developed a procedure for the stereoselective and diastereodivergent synthesis of densely functionalised cyclohexanes containing four stereocentres through an asymmetric Michael‐initiated ring closure (MIRC) cascade reaction employing hydrogen‐bond catalysis, which is able to prepare adducts with different absolute configurations starting from the same starting materials. The overall process involves a highly diastereo‐ and enantioselective Michael/Henry cascade reaction between a wide range of nitroal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 112 publications
1
26
0
Order By: Relevance
“…Carrillo and Vicarrio demonstrated a diastereodivergent Michael/Henry cascade reaction between α‐nitro‐δ‐oxo alkanoates and nitroalkenes employing 34 and 35 with the same squaramide backbone as catalysts. The cyclohexanes 36 and 37 with four adjacent chiral centers and inverse only at the C4 position were formed (Scheme ) . Generally, 36 were obtained in higher yields and stereoselectivities.…”
Section: Organocatalyst‐controlled Diastereodivergencymentioning
confidence: 99%
“…Carrillo and Vicarrio demonstrated a diastereodivergent Michael/Henry cascade reaction between α‐nitro‐δ‐oxo alkanoates and nitroalkenes employing 34 and 35 with the same squaramide backbone as catalysts. The cyclohexanes 36 and 37 with four adjacent chiral centers and inverse only at the C4 position were formed (Scheme ) . Generally, 36 were obtained in higher yields and stereoselectivities.…”
Section: Organocatalyst‐controlled Diastereodivergencymentioning
confidence: 99%
“…In this context, we have recently reported a catalytic and enantioselective Michael/Michael cascade reaction in which α-nitro-δ-ketoesters react with nitroalkenes to provide densely functionalized cyclohexanes in excellent yield and stereoselectivity ( Scheme 1 ) [ 27 ]. This reaction made use of bifunctional tertiary amine/squaramide catalysts [ 28 32 ] and, interestingly, we found that catalysts containing the same backbone chirality provided different diastereoisomers, thus allowing the development of a diastereodivergent process.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, it should be highlighted the area of organocatalysis, where enamine and iminium activation together with H-bonding catalysis strategy enable to carry out Michael/Henry cascade reactions with high efficiency and an exceptional level of control of the stereocenters formed in most cases. 2 In this context, and taking into account the experience acquired in our research group in the field of organocatalytic Michael/Henry reactions, 3 we decided to focus our studies on developing a Michael/Henry cascade process employing 2-nitromethylacrylates as suitable functionalized Michael donors with α,β-unsaturated aldehydes under iminium activation (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%